Exceptionality of Edge Graceful Labeling of Tricycle Graphs - S. Venkatesan; P. Sekar (International Journal of Mathematics And its Applications, 2017)
Graceful labeling is assignment of distinct labels from f{0, |E|} to vertices of graph, where edges are labeled by difference of absolute values of adjacent vertices and every label from f{1, 2, …, |E|} is used exactly once as an edge label. The edge - gracefulness is reversal of gracefulness. It involves labeling edges, rather than vertices, with an induced numbering consisting of sums of edge- labels, rather than differences of vertex labels. In this paper, we are discussing about exceptionality of edge graceful labeling of tricycle graphs by the verification by Lo's theorem.